Interatomic Coulombic decay in Neon-Helium cluster: a complex absorbing potential based equation-of-motion coupled cluster investigation - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2021)
The interatomic Coulombic decay (ICD) of the Ne(2s(-1)) and Ne(2s(-1)2p(-1)) states in neon-helium dimer is studied using highly accurate complex absorbing potential based equation-of-motion coupled cluster (CAP-EOMCC) method. The ICD decay process for the Ne(2s(-1)) state in neon-helium dimer is closed at its equilibrium bond distance. However, the decay channel is open at large bond distance of 6.2 angstrom. The decay channel for the double ionised Ne(2s(-1)2p(-1)) state is open at 3.46 angstrom. From our calculations, we have noticed that the decay rate of Ne(2s(-1)2p(-1)) state in neon-helium dimer is four times faster compared to the Ne(2s(-1)) state. We have also investigated how the decay rate of Ne(2s(-1)) state in neon-helium cluster varies in the presence of different helium environment. [GRAPHICS] .
Keywords: double ionised state; equation-of-motion coupled cluster (EOMCC); He droplet; interatomic Coulombic decay (ICD)